Manifestation of Tectonic and Climatic Perturbations in Deep-Time Stratigraphy – An Example From the Paleocene Succession Offshore Western Norway - Sømme, Tor Oftedal; Skogseid, Jakob; Embry, Patricia; Løseth, Helge (Frontiers in Earth Science, 2019)
Sediment routing systems may be exposed to different external controls that can modulate long and short-term sediment delivery to nearby basins. Here we investigate a Paleocene depositional system offshore western Norway that was subjected to long-term (∼10 Myr) tectonic perturbation and significant hinterland erosion. Superimposed on this long-term uplift, the system was also subjected to a short-lived climatic perturbation, which lasted ∼200 kyr. Regional 3D seismic reflection data is integrated with high resolution borehole and biostratigraphic data to map the stratigraphic responses to these different scales of perturbations on the Paleocene system. The initiation of the tectonic perturbation is marked by an angular unconformity in seismic data at the base of the Paleocene. An increase in sediment supply followed, causing progradation of a confined shelf-slope wedge during the Middle and Late Paleocene. The end of the tectonic perturbation is marked by onlap in the lowermost Eocene and a shift from a confined to a more lateral extensive depositional system. Calculations indicate that the tectonic uplift caused an order of magnitude increase in sediment supply to the basin. This period coincided with the Paleocene-Eocene Thermal Maximum (PETM), which is documented by biostratigraphic data as a discrete event within the overall regressive system. Although the PETM has been associated with increased continental runoff in the North Atlantic, no peak in sediment supply can be resolved in the available dataset. This study shows that the system response to tectonic perturbations may vary along strike, depending on the size of the routing systems and the antecedent topography prior to hinterland uplift. A low supply system may produce a tectonically linked shelf-slope wedge that is of similar thickness as a climatically linked wedge in a high supply system. This study documents how the same routing system responded to perturbations operating at different spatial and temporal scales and may help recognize similar process-response relationships in other areas.